Research on Optimizing the Safeguard System for "Three-Whole Education" (Full-staff, Whole-process and All-round Education) in Ideological and Political Education in Colleges and Universities in the New Era - Wang, Yutong (Education Insights, 2026)
In the context of the new era, deepening the enhancement of ideological and political education (IPE) in colleges and universities and implementing the comprehensive concept of "Three-whole Education"—namely full-staff, whole-process, and all-round education—is an essential pathway to fulfilling the fundamental task of cultivating virtue and nurturing talent, ultimately improving the overall quality of personnel training. However, the current safeguard system for IPE in many higher education institutions still suffers from significant limitations. These include an unclear division of responsibilities among various educational subjects, fragmented educational processes that disrupt continuity, insufficient integration of critical educational resources, and weak institutional and financial guarantees that hinder effective implementation. Based on a rigorous analysis of the core connotation and structural requirements of the "Three-whole Education" concept, this paper systematically identifies the practical dilemmas inherent in the existing safeguard mechanism. To address these challenges, the study proposes comprehensive optimization strategies from five key aspects: clarifying multi-subject responsibility mechanisms to ensure accountability, constructing a seamless whole-process education chain, integrating all-round educational resources for maximum impact, improving institutional and financial safeguards to provide robust backing, and empowering the entire system with advanced digital technology. These targeted measures aim to establish a highly scientific, well-coordinated, and sustainable safeguard system for IPE. Consequently, this framework will significantly promote the high-quality development and continuous advancement of ideological and political education in contemporary higher education environments.